2001
DOI: 10.1046/j.1432-1327.2001.02322.x
|View full text |Cite
|
Sign up to set email alerts
|

Galactofuranoic‐oligomannose N‐linked glycans of α‐galactosidase A fromAspergillus niger

Abstract: Extracellular a-galactosidase A was purified from the culture filtrate of an over-producing strain of Aspergillus niger containing multiple copies of the encoding aglA gene under the control of the glucoamylase (glaA) promoter. Endoglycosidase digestion followed by SDS/PAGE, lectin and immunoblotting suggested that glycosylation accounted for < 25% of the molecular size of the purified protein. Monosaccharide analysis showed that this was composed of N-acetyl glucosamine, mannose and galactose. Mild acid hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
4
37
1
Order By: Relevance
“…However, we cannot rule out the possibility of other hexoses. For example, in A. niger N-linked glycans, the presence of galactose in a galactofuranose conformation has been established (44,46). In this work, we did not analyze for their appearance by digestion with alternative mannosidases, such as an ␣-1,2/3/6-mannosidase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot rule out the possibility of other hexoses. For example, in A. niger N-linked glycans, the presence of galactose in a galactofuranose conformation has been established (44,46). In this work, we did not analyze for their appearance by digestion with alternative mannosidases, such as an ␣-1,2/3/6-mannosidase.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the glycans found resemble mammalian high-mannose glycans [Man (6)(7)(8)(9) GlcNAc 2 ]. In addition, typical "fungal-type" glycans that are structurally different from the mammalian glycans have been identified on different Aspergillus glycoproteins [Man (5)(6)(7)(8)(9)(10)(11)(12) GlcNAc 2 ] (1, 29,44,45).…”
mentioning
confidence: 99%
“…These were the average values from two determinations. Glycans of filamentous fungi are known to be of the high-mannose type, and terminal galactose, in the furanose form (Galf), has been observed on N-linked glycans from A. niger (29).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the presence of terminal Galf may be dependent on the culture conditions and may also be affected by the strain of A. niger used (18). It has been suggested that terminal Galf may be antigenic (29); therefore, elimination of this residue from glycan by an appropriate choice of a strain or manipulation of a strain would be beneficial. Since approximately half of the heavy chains were shown to be nonglycosylated, it is likely that some fraction, conceivably a major fraction, of assembled antibodies had one nonglycosylated heavy chain and one glycosylated heavy chain.…”
Section: Discussionmentioning
confidence: 99%
“…This isomer of galactose is absent in mammals and may be highly immunogenic in humans. 126 For a long time, plants were considered low-cost alternative for the production of recombinant proteins. In 1989, Hiatt and colleagues 127 were the first to demonstrate the production of a functional recombinant IgG1 in transgenic tobacco.…”
Section: Insect Cells System Vs Other Expression Systemsmentioning
confidence: 99%